The Role of R&D in Productivity Growth: The Case of Agriculture in New Zealand: 1927 to 2001 - Julia Hall; Grant M Scobie (New Zealand Government, The Treasury, 2006)
Productivity growth is a key determinant of rising living standards. The agricultural sector has been an important contributor to the overall growth of productivity in New Zealand. The average rate of multifactor productivity growth in agriculture from 1926-27 to 2000-01 was 1.8%. We find evidence that this rate has been increasing especially since the reforms of the 1980s. This paper estimates the contribution that R&D has made to agricultural productivity. It develops a theoretical framework based on the stock of knowledge available to producers. This model incorporates foreign stocks of knowledge and the spill-in effect for New Zealand. The estimation allows for extended lag effects of research spending on productivity. We find that foreign knowledge is consistently an important factor in explaining the growth of productivity. It appears that the agricultural sector relies heavily on drawing on the foreign stock of knowledge generated off-shore. The contribution of domestic knowledge generated by New Zealand's investment in R&D is less clear cut. However, there is typically a significant positive relation between domestic knowledge and the growth of productivity. We find a wide range of estimates of the return to domestic R&D. The results are sensitive to the type of model used and the specification of the variables. Based on our preferred model we estimate that investment in domestic R&D has generated an annual rate of return of 17%. The results underscore the importance of foreign knowledge in a small open economy. The very existence of foreign knowledge may be a necessary condition for achieving productivity growth in a small open economy. However in no way could it be argued that this was sufficient. Having a domestic capability that can receive and process the spill-ins from foreign knowledge is vital to capturing the benefits. The challenge is to be able to isolate those effects from aggregate data for the agricultural sector. In that task we claim only modest success.
Keywords: O30; O40; 330; New Zealand; technological change; R&D; productivity; economics of knowledge; spillovers; rates of return; agriculture